Cardiac Shock Wave Therapy Improves Ventricular Function by Relieving Fibrosis Through PI3K/Akt Signaling Pathway: Evidence From a Rat Model of Post-infarction Heart Failure - Wang, Luqiao; Tian, Xin; Cao, Yuting; Ma, Xuejuan; Shang, Leilei; Li, Hao; Zhang, Xueting; Deng, Furong; Li, Shumin; Guo, Tao; Yang, Ping (Frontiers in Cardiovascular Medicine, 2021)
Objection: Cumulative studies have identified the effectiveness of cardiac shock wave therapy (CSWT) in treating heart failure after acute myocardial infarction (AMI), but little have been discussed with regard to the beneficial effects of CSWT on anti-fibrosis along with the underlying mechanism. In this study, we investigated whether CSWT could reduce post-AMI fibrosis and further explored the molecular mechanism. Methods: Rat heart failure (HF) models induced by ligating the left anterior descending coronary artery were established and validated by echocardiography. Eligible animals were randomly categorized into five groups: the sham group, the HF group, the HF + CSWT group, the HF + LY294002 group, and the HF + CSWT + LY294002 group. The cardiac weight, serum level of BNP, NT-pro BNP and echocardiography parameters were measured to assess cardiac function in different groups. Masson's trichrome staining was used to assess the proportions of the fibrotic area. The expression level of CD34, αSMA was measured by RT-PCR, Immunohistochemistry and Immunofluorescent analyses and the level of PI3K/Akt was quantified by Immunohistochemistry and Western blotting. Results: The application of CSWT significantly improved cardiac function and reduced myocardial fibrosis and level of CD34 and αSMA, compared to the HF group. CSWT led to significant elevations of p-PI3K and p-Akt expression levels compared to that of the HF group and the inhibition of the PI3K/Akt pathway abolished the observed beneficial effects of CSWT. Conclusion: CSWT can facilitate the alleviation of cardiac fibrosis induced by AMI through the activation of PI3K/Akt signaling pathway.